Possibilities for sugar beet production in Southern Transdanubia - Csima, Ferenc (Acta Agraria Kaposváriensis, 1999)
Sugar beet yields almost the highest sales revenues among field crops. At an appropriate production level, sugar beet farms’ turnover per hectare can be many times more than that of grain crops. However, since it has limited marketability, sugar beet is more vulnerable to unfavourable market changes, and the size of cropping area is directly affected by the domestic sugar demand, any exports of sugar beet, concentrate and sugar, and the market conditions for sugar beet processors. From the early 1990s until the present day household sugar consumption has varied but on the whole stagnated. The quantity of sugar used by industry has decreased due to the ground gained by isosugar, and sugar beet exports to Croatia and Serbia have ceased. The unfavourable market trends have led to a decrease in sugar output: the sugar production capacity of Hungary which stood at 600,000 tonnes in the mid-1990s was only 64% utilised between 1992 and 1995. This has caused fierce market competition due to the declining demand, which, together with the sugar processors’ decisions to concentrate production in order to eliminate idle capacity, resulted in the closure of sugar refining plants, and, simultaneously, led to a decrease in the area of land devoted to sugar beet cropping. Sugar processing plants in different parts of the country can only be competitive if they are able to produce sugar cost-effectively, which, however, is subject to the quality of sugar beet to be processed. Sugar beet cropped by producers in the southern Transdanubian region surpasses the national average in terms of both quantity and quality, which signifies an adequate income for the croppers, and also better productivity than that of competitors and more economical sugar output for the Kaposvár sugar processing plant.
Keywords: comparative advantages; idle capacity; loss of export markets; concentration of production; output of quality products